2016
DOI: 10.4103/0972-4052.179322
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of sagittal condylar guidance by protrusive interocclusal records with panoramic and lateral cephalogram radiographs in dentulous population: A clinico-radiographic study

Abstract: Aim:To evaluate and compare the correlation between sagittal condylar guidance obtained by protrusive interocclusal records mounted on semi-adjustable articulator with panoramic and Lateral cephalogram radiograph tracings in dentulous population.Materials and Methods:One-hundred twenty dentulous subjects between age group of 20–40 years, free of signs and symptoms of any temporomandibular diseases were selected. The sagittal condylar guidance was determined by protrusive interocclusal records and transferred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
0
27
0
4
Order By: Relevance
“…(2016), where they found that panoramic radiographs showed a higher HCG value than that of lateral cephalogram. [24] This anomaly may be explained by the fact that these investigators had taken into account separately two lateral cephalograms of either side in dentulous population, while the present study attempted the tracings on lateral cephalograms which showed overlapping of the right and left sides as the sensor was present only in the right side. Reference measurement procedure based on unilateral image of lateral cephalogram may have directly affected on results in this study creating discrepancies with other two methods.…”
Section: Discussionmentioning
confidence: 98%
“…(2016), where they found that panoramic radiographs showed a higher HCG value than that of lateral cephalogram. [24] This anomaly may be explained by the fact that these investigators had taken into account separately two lateral cephalograms of either side in dentulous population, while the present study attempted the tracings on lateral cephalograms which showed overlapping of the right and left sides as the sensor was present only in the right side. Reference measurement procedure based on unilateral image of lateral cephalogram may have directly affected on results in this study creating discrepancies with other two methods.…”
Section: Discussionmentioning
confidence: 98%
“…Galagali et al . [11] also reported a correlation between the condylar guidance angles obtained by protrusive interocclusal records, panoramic radiograph, and the lateral cephalogram radiograph methods. They found that lateral cephalogram radiographs were more positively related than the panoramic radiograph, and the values of lateral cephalogram radiographs were closer to the interocclusal records on the articulator as separate radiographs for the left and right side were taken, making the amount and quality of image distortionless.…”
Section: Discussionmentioning
confidence: 97%
“…The guidance inclination in semi-adjustable articulators is set either by individual protrusive or lateral inter-occlusal registrations. Varying inclinations have been reported with consecutive registrations, between operators, between recording materials, and between articulators [3].…”
Section: Inroductionmentioning
confidence: 99%